The Effect of Topical 100% Sunflower Seed Oil (SSO) Extract on Trans Epidermal Water Loss (Tewl) and Skin PH Levels in a History of Atopic Dermatitis - Megawati, Yunitasari; Widayati, Retno Indar; Malik, Diah Adriani (Jurnal Health Sains, 2024)
The skin barrier function can be disturbed in various conditions, one of which is atopic dermatitis (AD). Efforts to improve the skin barrier can be done by using various types of moisturizers. Natural oil from sunflower seed oil (SSO) can be used as "skin barrier therapy" by reducing trans epidermal water loss (TEWL) and skin pH levels. A randomized single blind clinical trial with a two parallel group pre and post design was conducted on subjects with a history of AD who were treated at the Skin and Venereology Polyclinic at Sunan Kalijaga Hospital, Demak. Samples were randomized into 2 groups to receive 100% SSO or petrolatum as a control. TEWL and pH assessments were carried out at the beginning of the study and at week 4. Bathing habits and complaints about using moisturizers were also assessed. TEWL values ​​decreased in the SSO and petrolatum groups (-5.8±1.93 vs -6.1±9.08, p = 0.9). The pH value in AD patients also decreased after administration of SSO extract and petrolatum (-0.4±0.10 vs -0.2±0.75, p = 0.2). The decrease in TEWL and pH in both groups was not statistically significant. This may be related to differences in bathing habits and moisturizer use in the two groups. Most of the samples in the SSO group stated that they had no complaints regarding usage. The entire sample completed the study without any reports of allergic reactions or hypersensitivity. Administration of SSO extract was effective in reducing TEWL and pH in DA with the majority of samples stating that they had no complaints about use.